Physico-chemical characteristics of the oil from macauba kernels stored after drying at different temperatures - Marcela Silva Carvalho; Paulo Cesar Corrêa; Gutierres Nelson Silva; Adalberto Hipólito de Sousa; Lucas Martins Lopes (Revista Ciência Agronômica, 2022)
ABSTRACT Studies of post-harvest storage and drying in macauba fruit (Acrocomia aculeata (Jacq.) Lodd. Mart) are still in the early stages. The aim of this work was to investigate the effect of drying on the quality of macauba kernel oil during storage. Drying was carried out under three different air temperatures: 40°C, 50°C and 60°C. Four replications were used for each temperature. After drying, the kernels were stored for 0, 60, 120, 240 and 360 days, and the following physico-chemical analyses were carried out for each period: kernel oil content, acidity index, oxidative stability, water activity and oil colour. An increase in storage time resulted in an increase in the acidity index and a reduction in the oxidative stability of the oil in all treatments. The mean value for water activity in the oil ranged from 0.56 to 0.68. The mean values of the L* and b* coordinates did not differ from the control, except for the storage times of 0 and 60 days. There was a difference in the a* coordinate between the drying processes when compared to the control. No significant differences were seen for oil content. It was concluded that drying can be efficient tool in controlling the quality of kernel oil during storage.